SOG1, a plant‐specific master regulator of DNA damage responses, originated from nonvascular land plants. (27th December 2021) - Sakamoto, Ayako N.; Sakamoto, Tomoaki; Yokota, Yuichiro; Teranishi, Mika; Yoshiyama, Kaoru O.; Kimura, Seisuke
Abstract: The suppressor of gamma response 1 (SOG1), a NAM, ATAF1, 2, and CUC2 (NAC)‐type transcription factor found in seed plants, is a master regulator of DNA damage responses (DDRs). Upon DNA damage, SOG1 regulates the expression of downstream DDR genes. To know the origin of the DDR network in land plants, we searched for a homolog(s) of SOG1 in a moss Physcomitrium (Physcomitrella) patens and identified PpSOG1a and PpSOG1b . To assess if either or both of them function(s) in DDR, we knocked out the PpSOG1s using CRISPR/Cas9‐mediated gene editing and analyzed the responses to DNA‐damaging treatments. The double‐knockout (KO) sog1a sog1b plants showed resistance to γ‐rays, bleomycin, and ultraviolet B (UVB) treatments similarly seen in Arabidopsis sog1 plants. Next, we irradiated wild‐type (WT) and KO plants with γ‐rays and analyzed the whole transcriptome to examine the effect on the expression of DDR genes. The results revealed that many P. patens genes involved in the checkpoint, DNA repair, replication, and cell cycle‐related genes were upregulated after γ‐irradiation, which was not seen in sog1a sog1b plant. These results suggest that PpSOG1a and PpSOG1b work redundantly on DDR response in P. patens ; in addition, plant‐specific DDR systems had been established before the emergence of vascular plants.